Citrate anticoagulation: Are blood donors donating bone?. Issue 5 (26th November 2015) - Bialkowski, Walter; Bruhn, Roberta; Edgren, Gustaf; Papanek, Paula
Abstract : An estimated 2.4 million volunteer apheresis blood donation procedures were performed in the United States in 2010, and increases in the proportion of transfused blood products derived from apheresis blood collections have been consistently reported. Anticoagulation is required during apheresis and is achieved with citrate. Donor exposure to citrate causes an acute physiological response to maintain serum mineral homeostasis. Some data are available on the sequelae of this acute response in the days and weeks following exposure, raising questions about bone mineral density in regular apheresis donors. New research is emerging that addresses the potential long‐term health outcomes of repeated citrate exposure. This article reviews the acute physiological response to citrate anticoagulation in volunteer blood donors, presents contrasting perspectives on the potential effects of citrate exposure on bone density, and identifies key knowledge gaps in our understanding of long‐term health outcomes in apheresis donors. J. Clin. Apheresis 31:459–463, 2016. © 2015 Wiley Periodicals, Inc.